Pengaruh Peer Pressure dan Social Comparison Terhadap Kecenderungan Depresi pada Remaja di Boarding School X: Penelitian - Nur Satia Nasution; Tarmidi; Suri Mutia Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Adolescents living in boarding schools face unique social dynamics, where intensive peer interactions may trigger social pressure and self-comparison. This study aims to examine the effect of peer pressure and social comparison on depressive tendencies among adolescents in Boarding School X. A quantitative approach with a cross-sectional design was used. The respondents were 165 students aged 13–18 years. Data collection instruments included adapted versions of the Peer Pressure Inventory (PPI), the Iowa-Netherlands Comparison Orientation Measure (INCOM), and the Beck Depression Inventory-II (BDI-II). Data were analyzed using multiple linear regression. The results showed that peer pressure and social comparison simultaneously had a significant effect on depression (F = 19.202, p < 0.001) with a 19.2% contribution. Partially, social comparison had a significant positive effect on depression (t = 4.645, p < 0.001), while peer pressure had a significant negative effect (t = –3.162, p = 0.002). These findings indicate that in the boarding school context, peer pressure serves as a protective factor, while social comparison increases the risk of depression.